Europe and India: the need for greater mutual awareness - Rothermund, Dietmar (Asien, 2001)
The EC is poised to accept several East-European states as new members. In this way it will be preoccupied with its own integration and will not pay much attention to developments in distant places such as India. A consolidated "Little Europe" would certainly be more effective in dealing with the outside world, but it seems that nobody in Europe would opt for a minimal solution — least of all the East Europeans who wish to join the EC as soon as possible.
Elektronische Reproduktion der Druckausgabe
Keywords: Europäische Union; Indien